Respon Jamaah Haji terhadap Kualitas Pelayanan Kesehatan di Daerah Kecamatan Pademawu Kabupaten Pamekasan - Rahmah, Zainabur; Fitrianingsih, Avin Ainur; Rachma, Lailia Nur; Astari, Lina Fitria; Riskiyana, Riskiyana (Journal of Islamic Pharmacy, 2020)
The number of pilgrims of various ages and levels of education experience many health problems such as hypertension, respiratory infections and heart problems. From these problems encourage researchers to determine the response of prospective pilgrims to health services in Pademawu Pamekasan. The object of this study is the pilgrims in Pademawu Pamekasan Regency. The purpose of this study was to determine the response of the pilgrims in Pademawu District, Pamekasan Regency. This research uses a quantitative approach that is data collection using a questionnaire instrument. The sampling technique uses a total sampling population of 70 pilgrims. The study was conducted in the District of Pademawu Pamekasan to the Hajj pilgrims in 2018. The results of the study of the pilgrims' response to the quality of service include cognitive, affective, conative, age and education levels. Overall, the response of the haj pilgrims to the quality of service on the cognitive aspect was 29.5%. In the affective aspect of 4.69%. In the conative aspect 2.05%. At the age factor of 4.51% and at the aspect of Education level as much as 2.19%. The quality of health services affects the response of the pilgrims to the cognitive, affective and conative aspects but is not influenced by the age and level of education of the pilgrims.Keywords: hajj response, service, health